2017
DOI: 10.1101/212134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of sequence variant detection and bacterial DNA extraction methods on the measurement of microbial community composition in human stool

Abstract: BackgroundThe human gut microbiome has been widely studied in the context of human health and metabolism, however the question of how to analyze this community remains contentious. This study compares new and previously well established methods aimed at reducing bias in bioinformatics analysis (QIIME 1 and DADA2) and bacterial DNA extraction of human fecal samples in 16S rRNA marker gene surveys.ResultsAnalysis of a mock DNA community using DADA2 identified more chimeras (QIIME 1: 0.70% of total reads vs DADA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In addition, both of ASV methods detected all the true haplotype with 15/15 detection rate. The great performance of the ASV methods for eliminating false positive haplotypes is consistent with previous studies that identified microorganisms from mock community samples at fine taxonomical resolutions (Callahan et al 2016;Hughes et al 2017;Kopylova et al 2016). In previous studies, the detection of true/false haplotypes relied on known reference sequences , Parsons et al 2018, while the ASV-based approach used in the present study allowed us to distinguish true haplotypes from false positive haplotypes without the reference database.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, both of ASV methods detected all the true haplotype with 15/15 detection rate. The great performance of the ASV methods for eliminating false positive haplotypes is consistent with previous studies that identified microorganisms from mock community samples at fine taxonomical resolutions (Callahan et al 2016;Hughes et al 2017;Kopylova et al 2016). In previous studies, the detection of true/false haplotypes relied on known reference sequences , Parsons et al 2018, while the ASV-based approach used in the present study allowed us to distinguish true haplotypes from false positive haplotypes without the reference database.…”
Section: Discussionsupporting
confidence: 87%
“…The use of high-fidelity DNA polymerase in PCR contributes to decreased errors in PCR products (Ramachandran et al 2011), but it does not completely prevent the errors. The OTU methods involve clustering of sequences that are less different from each other than a fixed similarity threshold (typically 97%; Callahan et al 2016;Hughes et al 2017). Thus, true haplotypes that are similar to each other are clustered into a single OTU, leading to incorrect evaluations of intraspecific genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained sequence reads for each sample with no differences in read counts between the two storage conditions. To join the sequence reads and ilter low-quality reads, DADA2 was used through QIIME2, which is a fast and accurate tool for metagenomic analyses [21,35,36]. We observed a difference in the number of paired-end reads, suggesting that different storage conditions could yield different microbial information.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas the depiction of the frequencies of Gram‐negative bacteria was accurate among the four kits, there was some overestimation, especially with the strains of Bacillus and Lactobacillus . Previous studies (Yuan et al, 2012; Hughes et al, 2017; Ojo‐Okunola et al, 2020; Yang et al, 2020) had also observed a considerable overestimation of Lactobacillus sp. and Bacillus sp.…”
Section: Discussionmentioning
confidence: 86%